Digestibility of Feed Supplemented with Common Pleco Meal and Its Impact on The Growth of Nile Tilapia (Oreochromis sp.) - Andriani, Yuli; Pratama, Rusky Intan (Torani Journal of Fisheries and Marine Science, 2023)
Common pleco is a wild fish whose habitat occupies a lot of reservoir areas and public waters in Indonesia. The amount is abundant and not consumed by humans, is a great potential to be used as a source of animal protein in fish feed. The purpose of this study was to evaluate the digestibility of common pleco fish meal in artificial feed for nile tilapia (Oreochromis niloticus.) The study was carried out at the Aquaculture Laboratory Hatchery, Faculty of Fisheries and Marine Sciences, Universitas Padjadjaran, while the manufacture of common pleco meal, proximate analysis of feed ingredients and the test feed was carried out by the Laboratory of Chemistry and Animal Feed, Faculty of Animal Husbandry, Universitas Padjadjaran. The design used in this study was a Completely Randomized Design (CRD) consisting of 5 (five) treatments and 3 (three) replications. The treatment given was the addition of common pleco flour in artificial feed at 0%, 5%, 10%, 15% and 20%. The parameters observed in this study consisted of digestibility, growth rate, and water quality. The results of the research on some of these parameters indicate that the addition of common pleco meal can still be used in artificial feed up to 10%. The tilapia studied had the highest relative growth with a value of 0.218%. The digestibility level of the studied feed reached a value of 85.256%, and the water quality studied was still within the safe tolerance limits for fish farming. Based on the results of this study, the negative effect on the survival rate of tilapia did not occur until the addition of common pleco flour to artificial feed reached 10%. Thus, the fish meal has the potential as an alternative to fish meal in fish feed formulations.